2014
DOI: 10.1016/j.ajpath.2014.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocytes, Rather than Cholangiocytes, Can Be the Major Source of Primitive Ductules in the Chronically Injured Mouse Liver

Abstract: The proliferation of biliary lineage cells in chronic liver diseases, which leads to formation of primitive ductules in portal areas of the hepatic lobule, may be important not only for liver regeneration, but also for initiation of liver cancer. Thus, understanding how these primitive ductular cells emerge and proliferate in chronically injured liver holds promise for development of therapeutic strategies for liver diseases. However, the origin of these primitive ductular cells remains controversial. Here, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
105
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(115 citation statements)
references
References 31 publications
9
105
1
Order By: Relevance
“…Scale bar: 1,000 μm (low-magnification H&E, top panel, B); 500 μm (H&E mouse 1-3, B); 100 μm about 15%, further corroborating the conception that a minor portion of DRCs derive from hepatocytes. In contrast with our study and Yanger's study, Suzuki and colleagues proposed that the vast majority of all DDC-induced CK19 + DRs arise from the hepatocyte and not from the biliary compartment, even after short-term DDC treatment, when using the Alb-CreER strain (41) to specifically trace the hepatocyte compartment (9). To address these discrepancies, we used the identical Alb-CreER mouse strain (41) to analyze Cre activity in R26 Tom Alb-CreER animals.…”
Section: R26contrasting
confidence: 51%
See 1 more Smart Citation
“…Scale bar: 1,000 μm (low-magnification H&E, top panel, B); 500 μm (H&E mouse 1-3, B); 100 μm about 15%, further corroborating the conception that a minor portion of DRCs derive from hepatocytes. In contrast with our study and Yanger's study, Suzuki and colleagues proposed that the vast majority of all DDC-induced CK19 + DRs arise from the hepatocyte and not from the biliary compartment, even after short-term DDC treatment, when using the Alb-CreER strain (41) to specifically trace the hepatocyte compartment (9). To address these discrepancies, we used the identical Alb-CreER mouse strain (41) to analyze Cre activity in R26 Tom Alb-CreER animals.…”
Section: R26contrasting
confidence: 51%
“…Hence, ductular reactive cells (DRCs) arise periportally and express biliary proteins, such as CK19, EpCAM, CD133, SOX9, or A6 (rodents). However, hepatocytes may also give rise to DRCs by undergoing biliary metaplasia in response to injury (5)(6)(7)(8) and have recently even been proposed to be the main cellular source for DRs in distinct injury models (9).…”
Section: Introductionmentioning
confidence: 99%
“…Consistently, mutations in Jagged1 or its major receptor gene Notch2 lead to Alagille syndrome in humans, which is characterized by abnormal formation of the ductal network, causing jaundice 35. In addition to such a fundamental role in fetal liver development, several recent studies have indicated another functional role of Notch signaling in ductular hyperplasia (so‐called pseudoductal reaction) induced by feeding of a DDC diet and the biliary type of liver injury 36, 37. In contrast to those studies, the results of the present study showed that the extent of ductular cell proliferation was not altered by Jagged1 deletion in CCl 4 ‐induced fibrotic liver tissue (Fig.…”
Section: Discussionmentioning
confidence: 93%
“…In the previous studies, the contribution of Notch signaling to the pseudoductal reaction was suggested by using gamma secretase inhibitors and mice either overexpressing NICD1 or lacking the Notch target molecule Hes1 36, 37, 38. Therefore, it is unknown which Notch ligand(s) plays a central role in DDC diet‐induced ductular hyperplasia.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, good evidence now exists that hepatocytes can “transdifferentiate” into ductal biliary epithelial cells in certain injury models(Michalopoulos et al, 2005; Sekiya and Suzuki, 2014; Tanimizu et al, 2014; Yanger et al, 2013) and/or by forced genetic modulation of the developmentally important Notch (Jeliazkova et al, 2013; Yanger et al, 2013) and Hippo pathways(Yimlamai et al, 2014). In the context of cancer, multiple groups have shown that hepatocytes can be transformed into a biliary-cell-like tumor, cholangiocarcinoma, previously thought to originate exclusively from cholangiocytes(Fan et al, 2012; Sekiya and Suzuki, 2012).…”
Section: Introductionmentioning
confidence: 99%